2018
DOI: 10.1021/acs.est.7b05258
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Metals into Calcite in a Deep Anoxic Granite Aquifer

Abstract: Understanding metal scavenging by calcite in deep aquifers in granite is of importance for deciphering and modeling hydrochemical fluctuations and water-rock interaction in the upper crust and for retention mechanisms associated with underground repositories for toxic wastes. Metal scavenging into calcite has generally been established in the laboratory or in natural environments that cannot be unreservedly applied to conditions in deep crystalline rocks, an environment of broad interest for nuclear waste repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 67 publications
4
40
0
Order By: Relevance
“…Kelly et al (2003), however, found that U(VI) as uranyl (UO 2+ 2 ) was the dominant species in a natural sample of vein calcite, which they considered to be more representative of typical low-U material than the Sturchio sample. Drake et al (2018) found much higher concentrations of uranium in calcite precipitated from deep anoxic groundwater than experimental determinations that were performed in oxic conditions, and they interpreted this high uranium uptake as being due to the incorporation of U(IV) and thus that the partition coefficient for U(IV) in these envi-ronmental conditions is orders of magnitude larger than for U(VI). It is evident that more data from natural carbonates in different settings are needed to more fully understand the controls on U and Pb incorporation.…”
Section: U and Pb Contents In Carbonatementioning
confidence: 89%
See 1 more Smart Citation
“…Kelly et al (2003), however, found that U(VI) as uranyl (UO 2+ 2 ) was the dominant species in a natural sample of vein calcite, which they considered to be more representative of typical low-U material than the Sturchio sample. Drake et al (2018) found much higher concentrations of uranium in calcite precipitated from deep anoxic groundwater than experimental determinations that were performed in oxic conditions, and they interpreted this high uranium uptake as being due to the incorporation of U(IV) and thus that the partition coefficient for U(IV) in these envi-ronmental conditions is orders of magnitude larger than for U(VI). It is evident that more data from natural carbonates in different settings are needed to more fully understand the controls on U and Pb incorporation.…”
Section: U and Pb Contents In Carbonatementioning
confidence: 89%
“…Radionuclide incorporation in calcite is not well understood despite several decades of interest, primarily driven by the field of nuclear waste storage and characterisation (e.g. Langmuir, 1978;Milton and Brown, 1987;Sturchio et al, 1998;Reeder et al, 2000Reeder et al, , 2001Kelly et al, 2003;Weremeichik et al, 2017;Drake et al, 2018). This is because trace element incorporation in calcite does not rely on thermodynamically determined partition coefficients but on a large number of phenomenological variables, including trace element availability, calcite growth rate, temperature, pH, Eh, pCO 2 , and the Ca 2+ : CO 2− 3 ratio in solution, ionic size, and U complexation.…”
Section: U and Pb Contents In Carbonatementioning
confidence: 99%
“…Although it is commonly assumed, based on experimental observations, that calcite crystals will reprecipitate and homogenize during long-term interaction with fluids, observations from deep crystalline rock fractures show that zonation is sustained within crystals [64], with examples of >400 Ma old growth zonation [29] that has not been affected by dissolution-reprecipitation. The isotopic inventory of calcite crystals therefore serves as archives for processes in the fracture system over long time periods.…”
Section: Discussionmentioning
confidence: 99%
“…C and O isotope already existed for DZ1:-122 9 . Settings follow those described previously [67][68][69] . Spots were placed in areas in the crystals without micro-fractures or inclusions.…”
Section: Methodsmentioning
confidence: 99%